Discovery of a novel allosteric inhibitor scaffold for polyadenosine-diphosphate-ribose polymerase 14 (PARP14) macrodomain 2. Issue 11 (15th July 2018) - Moustakim, Moses; Riedel, Kerstin; Schuller, Marion; Gehring, Andrè P.; Monteiro, Octovia P.; Martin, Sarah P.; Fedorov, Oleg; Heer, Jag; Dixon, Darren J.; Elkins, Jonathan M.; Knapp, Stefan; Bracher, Franz; et al.
Graphical abstract: Abstract: The polyadenosine-diphosphate-ribose polymerase 14 (PARP14) has been implicated in DNA damage response pathways for homologous recombination. PARP14 contains three (ADP ribose binding) macrodomains (MD) whose exact contribution to overall PARP14 function in pathology remains unclear. A medium throughput screen led to the identification of N -(2(-9H-carbazol-1-yl)phenyl)acetamide (GeA-69, 1 ) as a novel allosteric PARP14 MD2 (second MD of PARP14) inhibitor. We herein report medicinal chemistry around this novel chemotype to afford a sub-micromolar PARP14 MD2 inhibitor. This chemical series provides a novel starting point for further development of PARP14 chemical probes.